The first Ironomyiidae from mid‐Cretaceous Burmese amber provides insights into the phylogeny of Phoroidea (Diptera: Cyclorrhapha). (12th December 2018) - Li, Xuankun; Yeates, David K.
Abstract: Macalpinomyia jiewenae gen. et sp.n. is described from the mid‐Cretaceous (∼99 Ma) amber of Myanmar. Macalpinomyia jiewenae is the first Oriental representative of the enigmatic family Ironomyiidae (Diptera: Phoroidea), currently known from a single extant genus restricted to southeastern Australia, plus a monotypic genus from Canadian amber and three controversial genera based on impression fossils from China, Mongolia and Russia. A phylogenetic analysis of all Phoroidea families, including all ironomyiid extant and extinct genera, corroborates the monophyly of Ironomyiidae, and Macalpinomyia gen.n. is assigned to the subfamily Sinolestinae. Cretonomyiinaesubfam.n., is erected to accommodate the basal lineage of Ironomyiidae. Lebambromyia acrai Grimaldi & Cumming, previously placed in Ironomyiidae, is supported as an early branching lineage of Platypezidae. Our topology proposes that Ironomyiidae is sister to the remaining Phoroidea. The phylogenetic results, in combination with the fossil ages and relevant molecular divergence time analysis, suggests that Ironomyiidae probably originated at least in the Berriasian of the Early Cretaceous (∼140 Ma). This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:5DFFC944‐1350‐418E‐BCDC‐BB87FC013D5D . Abstract : Ironomyiidae (Diptera: Phoroidea) is described from the mid‐Cretaceous (∼ 99 Ma) amber of Myanmar for the first time with Macalpinomyia jiewenae gen. et sp.n. A phylogenetic analysis of all Phoroidea families, including all ironomyiid genera, supports the monophyly of Ironomyiidae and suggests that Ironomyiidae is sister to the remaining Phoroidea. The relationships within Ironomyiidae are reconstructed, and Cretonomyiinaesubfam.n. is erected to accommodate the basal lineage of the Ironomyiidae.